Idealizations and Understanding: Much Ado About Nothing?. Issue 4 (2nd October 2019) - Sullivan, Emily; Khalifa, Kareem
Abstract: Because idealizations frequently advance scientific understanding, many claim that falsehoods play an epistemic role. In this paper, we argue that these positions greatly overstate idealizations' import for understanding. We introduce work on epistemic value to the debate surrounding idealizations and understanding, arguing that idealizations qua falsehoods confer only non-epistemic value to understanding. We argue for this claim by criticizing the leading accounts of how idealizations provide understanding. For each of these approaches, we show that: (a) idealizations' false components promote only convenience instead of understanding and (b) only the true components of idealizations have epistemic value.